The role of shareholder activism in turning around poor performing target companies on the JSE: A case of Value Capital Partners - Mlamleli, Akona (University of the Witwatersrand, Johannesburg, 2025)
There is a rising trend of shareholder activism led by activist investors who acquire minority stakes in poorly managed companies with promising business models. The study explores the rising trend of shareholder activism, in which activist investors acquire minority stakes in poorly managed but promising companies to address governance and performance issues. This surge in investor activism, driven by environmental, social, and governance concerns and minority investor rights, aims to enhance the long-term competitiveness of target firms. Focusing on Value Capital Partners, South Africa's first hedge fund activist investment firm, the research evaluates the company’s impact on selected firms from 2014 to 2024. Specifically, it examines Value Capital Partners’ strategies, collaboration with management, and campaign outcomes, using financial reports and investor communications to assess the effectiveness and sustainability of its interventions. The study analyses changes in share prices, financial metrics, and strategic directions to determine the influence of hedge fund activism on corporate performance. Findings indicate that Value Capital Partners generally achieved positive outcomes during the study period, demonstrating the potential of hedge fund activism to improve corporate performance in South Africa. However, impact varied across companies, highlighting both successes and challenges. The research underscores the role of activist investors in promoting sustainable growth and sheds light on the elements that both enhance and hinder their success and lastly suggests future research directions to optimise activist investment strategies in the region.
A research report submitted in fulfillment of the requirements for the Master of Commerce (50%) in Finance, in the Faculty of Commerce Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Shareholder activism; Value Capital Partners; JSE; SDG-8: Decent work and economic growth; SDG-16: Peace, justice and strong institutions